Comparative Analysis of Agro Waste Material Solid Biomass Briquette for Environmental Sustainability. (19th May 2022) - Velusamy, Sampathkumar; Subbaiyan, Anandakumar; Murugesan, Senthil Rajan; Shanmugamoorthy, Manoj; Sivakumar, Vivek; Velusamy, Parthiban; Veerasamy, Senthilkumar; Mani, Kanitha; Sundararaj, Premkumar; Periyasamy, Selvakumar
Abstract : The agro waste briquettes produced from sorghum panicle and pearl millet with corn starch as the binder with varied proportions were compared with the other agro briquettes, and the elemental analysis of SP-PM briquettes was compared with the agro waste, palm kernel shell, soybean waste, mango leaves, rice husk, spruce, and coffee husk briquettes. The TGA results of SP-PM briquettes were compared with the corn leaf, baggase, almond shell, banana leaves, banana pseudostem, pineapple leaf, stem and root, low rank coal, bituminous coal, cotton stalk, and wheat straw. The DSC analysis that was carried out for SP-PM briquettes were compared with the rice husk char, spent coffee ground, wood chips, saw dust, wood straw, Tomsk peat, Sukhovskoy peat, Arkadievsky peat, nutshell, and bran. Thus, the briquettes made out of sorghum panicle and pearl millets are compared with the other biomass briquettes for its efficiency and its quality. Thus, the briquettes made out of sorghum panicle and pearl millets are compared with the other biomass briquettes for its efficiency and its quality.